Comparative Analysis of the Effectiveness of Different Options for the Administration of Cardioplegic Solution during Surgical Correction of an Aortic Aneurysm Combined with Coronary Artery Lesions - Zhekov, Ihor I.; Sarhosh, Oleh I.; Grytsiuk, Andrii V.; Perepeliuk, Andrii I.; Rudenko, Anatoliy V. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To determine the effectiveness of myocardial protection in various variants of administration of cardioplegic solution in patients with aortic aneurysms combined with coronary artery lesions. Materials and methods. We analyzed 111 operations for aortic aneurysms combined with lesions of the coronary arteries, which were performed from 2011 to 2020 at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. The subjects were divided into four groups: group 1 where all three methods of cardioplegic solution administration (antegradely, retrogradely and into alloshunts) were used (60 [54.1%] patients), group 2 with administration of cardioplegic solution retrogradely and into alloshunts (48 [43.2%] patients), group 3 with antegrade and retrograde administration (2 [1.8%] patients), and group 4 with only retrograde administration of cardioplegic solution (1 [0.9%] patient). Of these operations, 19 (17.1%) were performed for acute type A aortic dissection, 4 (53.6%) for chronic type A aortic dissection, 88 (79.3%) for aortic aneurysm without dissection. The most common surgical interventions performed were: Robicsek procedure (41 [36.9%] interventions), Bentall – de Bono procedure (40 [36.0%] interventions), supracoronary ascending aortic replacement (22 [19.8%] operations), Wheat procedure (7 [6.3%] interventions). Results. According to our results, the aortic cross-clamp time was longer in group 2 (p < 0.05). The average time of extubation in groups 1 and 2 did not differ significantly (p > 0.05). At the same time, the average time of stay of patients in the intensive care unit differed significantly (p < 0.05) in patients of groups 1 (168.92 ± 121.54 h) and 2 (199.35 ± 214.42 h), which indicates faster recovery of patients of group 1. We diagnosed a total of 34 (30.6%) complications in 111 operated patients. A significant number of complications, namely 20 (33.3%) cases, were observed in group 1. The most frequent complications in this group were atrial fibrillation which occurred in 4 (6.7%) cases and hemorrhagic complications which were observed in 3 (5.0%) cases; of these, 1 (1.7%) case was with hemothorax and hemopericardium (this patient underwent rethoracotomy), 1 (1.7%) with hemopericardium and tamponade, and 1 (1.7%) with hemothorax. Of the 111 operations analyzed, 5 (4.5%) cases turned out to be fatal. Conclusions. The most effective method of introducing a cardioplegic solution in surgical interventions for aortic aneurysms combined with coronary artery lesions is the administration of cardioplegic solution antegradely, retrogradely and into alloshunts, after anastomosing thereof. This technique allows for the most effective protection of the myocardium by reducing the period of ischemia. In other cases, when it is impossible to introduce a cardioplegic solution antegradely (due to dissection of coronary arteries) or retrogradely (due to the presence of a persistent left superior vena cava), it is advisable to use all available alternative methods of protection and, if possible, to reduce the aortic cross-clamp time.